Use and evaluation of a non-alcoholic beverage based on cocoa mucilage and placenta of Thoebroma cacao L, Ananas comosus and mango Mangifera indica - Loor Vélez , Yelitza Marianela (2023)
The present research was conducted with the aim of taking advantage and evaluating the cocoa mucilage and placenta (Theobroma cacao L) in the formulation of a non-alcoholic beverage in combination with yellow fruits, pineapple (Ananas comosus), and mango (Mangifera indica). Physical-chemical analyses were carried out according to NTE INEN 2304:2017 to determine °Brix, pH, titratable acidity, sensory analysis attributes in consumers such as odour, colour, appearance, and consistency. A random design (AAC) was applied, with six treatments and three repetitions. We established the statistical differences between the means of the treatments with the Tukey test (P>0.05). The best formulation of the combination of non-alcohol beverages range with yellow fruits, pineapple (Ananas comosus) and mango (Mangifera indica) are T1 and T4 present preference in colour, smell, appearance, and consistency. The best cost/benefit ratio is T1, for every dollar invested returns 0.604 cents for a 1 L drink.